Masks of violence. Visuality and politics in the images of Ni una muerte indiferente (English version) - Bertolaccini, Luciana María (Nawi, 2024)
The aim of this paper is to analyze the images of an urban protest intervention called Ni una muerte indiferente (Not one indifferent death) carried out by “Mujeres de Negro Rosario”, Argentina, in November 25, known as the international day for the elimination of violence against women (redefined as the international day for the elimination of violence against women, lesbians, trans, transvestites and non-binary people). With this purpose, we will explore the expressive tools used, with a special focus on the use of masks and their ways of inscription in the public space. Likewise, we will study the relationship between violence and image, based on the analysis of the configuration and perception of the deaths that are propitiated there; the tension between presence and absence; the game between the singular-universal pair; and, finally, the link that is possible to think between image and testimony. Spanish version: https://nawi.espol.edu.ec/index.php/nawi/article/view/1010/1066